AN ANALYSIS OF DISTRIBUTION AND DIFFICULTY LEVELS OF LINGUISTIC QUESTIONS ON COGNITIVE DOMAIN IN INDONESIAN SUBJECT AT GRADE EIGHT OF SMP 1 TAKENGON - Harfiandi Harfiandi (Master Bahasa, 2020)
This study aims (1) to describe the distribution of linguistic questions of cognitive domain on the second semester final exam year 2013/2014 in Indonesian subject at Grade Eight of SMP 1 Takengon and (2) to describe the difficulty levels of linguistic questions of cognitive domain on the second semester final exam year 2013/2014 in Indonesian subject at Grade Eight of SMP 1 Takengon. The method used in this research is a quantitative descriptive. Data were obtained through documentation techniques. The results of this study show that (1) there are several levels the distribution of linguistic questions of cognitive domain on the second semester final exam year 2013/2014 in Indonesian subject at Grade Eight of SMP 1 Takengon i.e. C1 level items at 54% classified as unbalanced, C2 level items at 23% classified as unbalanced, C3 level items at 17% classified as unbalanced, and C4 level items at 6% classified as unbalanced and (2) there are the difficulty levels of linguistic questions of cognitive domain on the second semester final exam year 2013/2014 in Indonesian subject at Grade Eight of SMP 1 Takengon i.e. category of the easy items at 57% classified as unbalanced, category of the medium items at 37% classified as unbalanced, and category of the difficult items at 6% classified as unbalanced. From results of this study proved that (1) the distribution of linguistic questions on cognitive domain not balanced by the percentage proportion balancing of the items for grade of the SMP and (2) the difficulty levels of linguistic questions on cognitive domain not balanced by the percentage proportion balancing for amount of the items. Thus, an evaluation of distribution and difficulty levels of linguistic questions on cognitive domain on the second semester final exam year 2013/2014 in Indonesian subject at Grade Eight of SMP 1 Takengon still require adjustments in the future.